O acordo sobre os aspectos dos direitos de propriedade intelectual relacionados ao comércio (TRIPS): Implicaç\~oes e possibilidades para a saúde pública no Brasil - André de Mello e Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) came into force in 1995 in the ambit of the World Trade Organization (WTO). TRIPS obliges WTO country members to adopt higher standards of patent protection and, as a consequence, increases the costs of access to technological innovations, including in the pharmaceutical sector. The agreement thereby threatens public health policies, especially in developing countries. This study discusses the main implications of TRIPS to the Brazilian AIDS treatment program. The sustainability of this program has been ensured through local generic production, which not only has allowed for the import substitution of expensive antiretrovirals unpatented in Brazil, but also the attainment of significant price discounts for antiretrovirals that are patented in the country by pharmaceutical multinationals as they respond to government threats of compulsory licensing. However, this strategy has been exhausted, mainly as result of the lack of investments in the production of antiretrovirals in Brazilian labs. The reaction of the US, which has opened a panel against Brazil in the WTO but later withdrew it almost unconditionally, is also discussed. Brazil's efforts to make patent rights more flexible in the ambit of international negotiations, which attempted to associate patents with public health and human rights, benefited from the important support of transnational activist networks, and were generally successful, are also presented. The so-called Doha Declaration, which prioritizes health policies to the detriment of patent rights, constitutes the main achievement of Brazilian diplomacy in these negotiations. Finally, considerations are offered on how the country can better exploit the flexibilities offered by TRIPS in order to ensure the sustainability of its AIDS treatment program, concluding that importation from India will become increasingly difficult and that such program depends crucially on further investments in the technological capacitating of the Brazilian pharmaceutical industry.
Keywords: F13; F55; H51; I18; 330; TRIPS; Gesundheitsvorsorge; Pharmazeutische Industrie; Brasilien